TROPION-Lung08: phase III study of datopotamab deruxtecan plus pembrolizumab as first-line therapy for advanced NSCLC - Levy, Benjamin P; Felip, Enriqueta; Reck, Martin; Yang, James Ch; Cappuzzo, Federico; Yoneshima, Yasuto; Zhou, Caicun; Rawat, Siddhartha; Xie, Jingdong; Basak, Priyanka; Xu, Lu; Sands, Jacob (Future oncology (London, England), 2023)
Pembrolizumab monotherapy is a standard first-line treatment for PD-L1-high advanced non-small-cell lung cancer (NSCLC) without actionable genomic alterations (AGA). However, few patients experience long-term disease control, highlighting the need for more effective therapies. Datopotamab deruxtecan (Dato-DXd), a novel trophoblast cell-surface antigen 2-directed antibody-drug conjugate, showed encouraging safety and antitumor activity with pembrolizumab in advanced NSCLC. We describe the rationale and design of TROPION-Lung08, a phase III study evaluating safety and efficacy of first-line Dato-DXd plus pembrolizumab versus pembrolizumab monotherapy in patients with advanced/metastatic NSCLC without AGAs and with PD-L1 tumor proportion score ≥50%. Primary end points are progression-free survival and overall survival; secondary end points include objective response rate, duration of response, safety and presence of antidrug antibodies. : NCT05215340 (ClinicalTrials.gov).